Linguodidactic and psycholinguistic aspects of reading competence in foreign language teaching - Kurbanbayeva , Dilnoza (The Lingua Spectrum, 2025)
This article explores the formation of reading competence in foreign language education through linguodidactic and psycholinguistic lenses. The linguodidactic perspective provides a theoretical and methodological foundation for the development of reading skills, emphasizing the structured acquisition of lexical and grammatical knowledge and its application in text-based instruction. Simultaneously, the psycholinguistic approach investigates the cognitive and affective mechanisms involved in reading, including perception, memory, decoding, and semantic processing. The study underscores the need for integrative instructional strategies that foster critical engagement with texts, enhance language awareness, and support independent learning. Furthermore, the article highlights how the interaction between linguistic input and mental processes facilitates deeper comprehension and retention. By synthesizing these approaches, the paper presents a comprehensive framework for developing students’ reading competence in a foreign language, which aligns with contemporary pedagogical models that emphasize learner autonomy, intercultural awareness, and reflective thinking.